Field notes contributed by Robert K. Myers, spring 1985 - Myers, Robert K.et al (1985)
The field notes list various bird sightings by Myers, and sometimes others, and discusses the spring's disappointing migration, including a low number of warbler sightings. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly Report of spring 1985. Epson - sheet feed